PENGARUH PEMBERIAN MINYAK ZAITUN TERHADAP STRETCH MARK IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS PAUH KAMBAR - RISHEL, RIKA ASTRIA; ZAYANI, NOFRI; MAIFITA, YESI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Stretch marks are a common health problem in postpartum mothers. Stretch marks can appear in the mother's stomach area due to hormonal changes and skin stretching due to the increasing pregnancy. Management of stretch marks with non-pharmacological measures can be done with natural ingredients such as using olive oil. Olive oil which is rich in antioxidants and vitamin E can reduce itching, heat, dryness, and irritation. The purpose of this study was to determine the effect of giving olive oil to reduce stretch marks in postpartum mothers in the Pauh Kambar Health Center Work Area. The type of research is quantitative with a pre-experimental design with a one group pretest posttest approach. The research was conducted at the Pauh Kambar Health Center on July 22 - August 22, 2024. The population in this study were 15 postpartum mothers. The research sample was 15 postpartum mothers with a total sampling technique. The research instrument was an observation sheet. Data analysis was carried out using a paired t-test at the α = 5% level. The results of the study found that most postpartum mothers experienced stretch marks striae 3, namely 7 people (46.7%) before being given olive oil. After being given olive oil, the stretch marks formed were many striae 2, there were 8 people (53.3%). Bivariate analysis with paired t-test showed a p-value = 0.000 <α = 0.05 which means that there is an effect of giving olive oil on stretch marks in postpartum mothers in the Pauh Kambar Health Center work area. In conclusion, giving olive oil has an effect on stretch marks experienced by mothers in postpartum mothers in the Pauh Kambar Health Center work area. Suggestions for health workers should increase the provision of counseling once a month to postpartum mothers regarding stretch marks so as to reduce the fear of pregnant women.